Does the @home team reduce local Emergency Department attendances? The experience of one London service. (September 2019) - Pickstone, Nicola; Lee, Geraldine A.
Highlights: The multi-disciplinary @home team offers patients acute care in their homes. 1084 patients were referred to @home over 3 months. @home prevented 387 patients from attending ED. Abstract: Background: Since 2014, the @home team has been offering patients acute care in their own homes using a multi-disciplinary team with the aim of preventing some Emergency Department (ED) attendances, facilitating early discharges, and preventing acute admissions. By preventing some ED attendances, the @home team aims to contribute to the performance of the two local EDs, both of which are currently failing to meet the ED 4-h operational target. Objectives: To determine if the @home team reduces ED attendances locally, and if so, by how much, and whether this impacted on the 4-h operational target. Methods: The number of @home referrals that were prevented from attending either St Thomas's or King's College Hospital EDs was audited using a specially developed audit tool and spatial analysis performed, mapping the home locations of patients referred, and using 'nearest neighbour analysis' to determine the number and percentage of @home referrals prevented from attending the two local EDs. Results: A total of 1084 patients were referred to the @home team in a 3-month period with 755 (72%) referrals accepted. Using Geo-codable data, 387 local ED attendances were prevented (298 from King's College Hospital and 89 from St Thomas's Hospital ED). Over the same time period, King's College Hospital had 71, 688 ED attendances and St Thomas's ED had 48, 030 attendances. Conclusions: Although the @home team reduces a small number of ED attendances each month (1 in 300), this number is not high enough to make a significant impact on average performance against the 4-h target at the local EDs alone.